The Impacts of the COVID-19 pandemic on private dental practice in Uyo, Akwa-Ibom State, Nigeria - Nnaji, Chukwuemeka Emmanuel; ADAMU, VE (Orapuh Journal, 2022)
Introduction Due to the extremely contagious nature of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2), and because dental operations frequently generate blood and saliva droplets that could spread the virus, the Nigerian Dental Association (NDA) strongly advised all private dental clinics unable to procure the basic PPE or COVID-19 test kits to close down completely until adequate arrangements were made for such essential supplies. As a result of this recommendation, many private dental care providers suspended their services. This study aimed to assess the impacts of the COVID-19 pandemic on private dental practice in Uyo, Akwa-Ibom State, Nigeria. Materials & methods We used a 4-point Likert scale questionnaire to gather data on the impacts of the COVD-19 pandemic on the practice of 10 dental health care providers (DHCPs), using the following attributes: Very Great Extent (VGE), Great Extent (GE), Low Extent (LE), and Very Low Extent (VLE). We also collected the demographic information of the DHCPs. The results were analysed, using the 4-point Likert scale measurements and simple percentages. Results 90% of the respondents affirmed that the pandemic had beneficial impacts on their infection control measures while 95% indicated that the pandemic reduced patients’ dental visits. In addition, 77.5% of the respondents affirmed that the pandemic had detrimental impacts on their mental health. Similarly, many of the respondents (87.5%) concluded that the pandemic strained their relationships with patients and coworkers, while almost all the respondents (97.5%) claimed that the pandemic decreased their income. Conclusions We hope that this study will aid dental and other healthcare providers in better understanding the impacts of the COVID-19 pandemic on dental practice and strengthen relevant awareness across the oral healthcare system.